2015
DOI: 10.1111/jep.12404
|View full text |Cite
|
Sign up to set email alerts
|

A provincial adaptation of clinical practice guidelines for depression in primary care: a case illustration of the ADAPTE method

Abstract: The ADAPTE methodology provided structure, rigour and efficiency to the trans-contextual adaptation of guideline recommendations. We will share the challenges associated with the adaptation of clinical recommendations and organizational strategies for a mental health guideline, and the dissemination of the practice protocol in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Patient‐centered or “person”‐centered care and consideration of the patient's experience are vital components of proper ethical and modern evidence‐based health care. Similar recommendations were reported in other case studies for ADAPTE CPGs …”
Section: Discussionsupporting
confidence: 86%
“…Patient‐centered or “person”‐centered care and consideration of the patient's experience are vital components of proper ethical and modern evidence‐based health care. Similar recommendations were reported in other case studies for ADAPTE CPGs …”
Section: Discussionsupporting
confidence: 86%
“…Our review of the literature has confirmed that there is increasing interest in adapting guidelines around the world . Most of these examples are from developed settings and not all of them end up with building a new revised tool.…”
Section: Discussionmentioning
confidence: 68%
“…It is known that CAN‐IMPLEMENT was derived from the original ADAPTE Manual for cancer guidelines. ADAPTE has been used in several settings . Although, we did not compare 2 resources systematically via content analysis, we carefully reviewed both resources anddecided to use ADAPTE for the study purpose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations